Analysis Of The Effect Of Rising Costs And Falling Prices On The Financial Viability Di Perkebunan Kelapa Of Oil Palm Plantations Ptpn Iv, Kebun Melati, Kecamatan Pegajahan And Perbaungan Districts, Serdang Bedagai - Saprida, Saprida (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
This research discusses the Sensitivity Analysis of the Effect of Cost Increases and Price Decreases on Financial Feasibility in Oil Palm Plantation. Financial Feasibility is a tool used to analyze a business/project to determine whether or not a company is feasible in running its business, by examining the potential profits obtained from an investment/business. This research was conducted at PTPN IV oil palm plantation, Melati Plantation, Pegajahan and Perbaungan Districts, Serdang Bedagai Regency, North Sumatra Province. The research was conducted in June 2024, and the determination of the location was carried out intentionally (purposive) with the consideration that this area is one of the areas that have many oil palm plantations. In this study, researchers used two data, namely primary data and secondary data, where primary data was obtained through a direct interview process by asking questions that had been made, and then the relevant Plantation would provide a verbal response or written response represented by the Plantation Manager, This research uses a type of Quantitative research, which analyzes data by calculating data (in the form of numbers) obtained as it is (Real Price). This research uses a financial feasibility analysis method consisting of npv, net b/c, irr, and pbp. From the results of the research conducted, it can be concluded that the financial feasibility during the economic period of Oil Palm obtained, namely, NPV of Rp. 153,626,694,000, - Net B / C of 2.64, IRR of 21.03%, and Payback Period of 4 years 5 months. Sensitivity Analysis to 10% Price Decrease obtained Net Benefit Ratio (B/C) of 2,18 Net B/C>1, Internal Rate of Return (IRR) of 15,04% and Payback Period (PP) of 5 years 1 month. Sensitivity Analysis to 10% Cost Increase obtained Net Benefit Ratio (B/C) of 2,45 Net B/C>1, Internal Rate of Return (IRR) of 18,27% and Payback Period (PP) of 4 years 8 months.